Menumbuhkan Tunas Kreativitas: Strategi Pembelajaran Pendidikan Pancasila yang Efektif untuk Kelas 1 SD/MI - Maysurin Ni'amah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Education is the main foundation in forming the character and intelligence of the nation's next generation. In Indonesia, Pancasila education has a very important role in directing students' moral and ethical development from an early age. Therefore, this research was conducted to analyze effective Pancasila education learning strategies for grade 1 SD/MI. This research is qualitative research that uses the literature review method with Google School as a database. Based on the literature review that has been carried out, it can be concluded that creative learning methods, such as stories, games and art activities, are very effective in increasing grade 1 SD/MI students' understanding of the values ​​of Pancasila. These methods not only make the learning process more interesting and enjoyable, but also help students internalize the values ​​taught, develop critical thinking and problem solving skills, and form character in accordance with the principles of Pancasila. The successful implementation of creative learning methods is very dependent on the role of the teacher, family support and the school environment. Therefore, joint efforts are needed from various parties to overcome challenges and maximize the potential for creative learning in Pancasila Education.